(untitled) (Global Journal of Human-Social Science, 2020)
During the early Vedic period Indian women enjoyed equal status with men in all field of life. They enjoyed freedom in selecting their life partners. They had the right to get education. Remarriage of widows were permitted. Men did not have the right to divorce their wives. They were given the complete freedom in all aspect of family matters. There was no pardha system in hindu society. However their position got deteriorated during Mughal rule in India as they had not been paid sufficient attention which they deserved. Thereafter, the status of women in the beginning of the British rule reached at the worst level. However in mid nineteenth century some socio-religious reforms movements started by Raja Ram Mohan Rai, Swami Dayanand, and Swamy Vivekanand. Due to their efforts the position and status of women started improving in some instances. Thus, when the Constitution of India was being framed the constitution makers took inspiration from these eminent personalities and expressly provided special provisions in the var ious parts of the constitution which provides equality for women in all aspects of their life. This paper depicts the issues and challenges in empowering the women and suggests some ways of empowering women. This paper also highlights the role of law in empowering women.